Disaster preparedness plan for the local government records of Marikina City - Ariñas, Ma. Virginia L.; Cabbab, Johann Frederick A. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2014)
The Marikina City Government does not have a written general disaster plan for vital records stored per department. Protection and preservation of vital records per department depends on their head departments' or records officers' discretion in times of natural and man-made disasters. Having a written disaster plan for records stored in every department will assure the safety of its vital records.
This study sought to accomplish the following objectives: to find out the nature in terms of format, content and functions of vital records stored per department; to look at the current state of their vital records in terms of preservation and storage; to find out the procedures done per department holding vital records before, during, and after man-made and natural disasters; and to give recommendations of what can be made for the improvement of the disaster preparedness of the staff to protect the vital local government records.
The study was descriptive in nature. It was analysed according to the results of the gathered data per department holding vital records with its format, content, and preservation/storage. Risk analysis was also part of the study to find out the man-made and natural disasters that might affect the departments' records and how they are prepared to encounter such incident. With their existing disaster preparedness plan stored within their offices, recommendations to implement additional preventive and preparedness procedures was done.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Emergency management -- Philippines -- Marikina City; Local government publications -- Philippines -- Marikina City